Why American Minorities go to the Entrepreneurship? (Global Journal of Management and Business Research, 2016)
In this paper, I have studied the situation of small businesses that owned by ethnic minorities in the United States. I choose the African-American women as a sample to examine the position of their small businesses. Literature review and interactive interviews were used to find the best results. I went through the obstacles faced their businesses and how minorities were affected by the recession. Also, the reasons for increasing the number of entrepreneurs in the recent period, especially African-American women. The paper will end with statistical comparison and the reasons women choose entrepreneurship.
Keywords: entrepreneurship; recession; minority; unemployment; african american women